Computer Analysis of Energy and Resource Efficiency in the Context of Transformation of Petrochemical Supply Chains - Shinkevich, Alexey I.; Galimulina, Farida F.; Polozhentseva, Yulia S.; Yarlychenko, Alla A.; Barsegyan, Naira V. (International Journal of Energy Economics and Policy, 2021)
The purpose of this study is to identify areas of energy-efficient development in petrochemical supply chains through the use of computer analysis tools. The study uses system approach methods, comparisons, vertical dynamic analysis, economic and mathematical modeling, forecasting, factor analysis. Listed implementation methods helps to meet number of scientific results: systematized programs are applicable for petrochemical product supply management chains, as well as for a number of methods and algorithms developed by the authors in the framework of ensuring resource-saving development of petrochemical enterprises; dynamics assessment of supply chains’ petrochemical products in terms of energy consumption and energy efficiency consumption indicators; a production function expressed in the form of dependence of the production energy efficiency between the factors of capital (Costs per 1 ruble of sold products) and labor (Labor intensity) is proposed, allowing rational planning in the parameters of the production and logistics system of the PJSC "Nizhnekamskneftekhim" enterprise; a factorial model is developed, as a result of which two factors (energy and economic) formed energy resource efficiency indicator of petrochemical supply chains is proposed. As a result, promising directions for reducing energy intensity production and improving of supply chains for petrochemical products energy efficiency are identified. Keywords: petrochemical products, supply chains, energy resource efficiency, energy saving, energy intensity of production JEL Classifications: Ðž14, D24, Ð¡41 DOI: https://doi.org/10.32479/ijeep.11270